Aligning key performance indicators with lean management in the service sector: A case study for a Jordanian telecommunication company. Issue 1 (31st December 2022) - Alalawin, Abdullah; Qamar, Ahmad M.; AlAlaween, Wafa' H.; Bentahar, Yasser; Al-Halaybeh, Tarneem; Al-Jundi, Salsabeel; Tanash, Moayad
Abstract: Lean implementation in the service sector has a dilemma related to defining the gap of the lean system and identifying the flaws in the processes which affect the overall performance and efficiency. This paper presents an innovative model that can help service companies to improve lean implementation and integrate appropriate Key Performance Indicators (KPIs) with the strategic goals. The aim of this paper is to also investigate different forms of waste that affect services performance by using the data of a global best practice. It also aims to apply and integrate the KPIs with Lean Management Tools to overcome the potential limitations of the traditional ones. As a first step of improvement, designing a new KPI lean method can lead to determining and reducing all different forms of existing wastes. Furthermore, such a method is expected to (i) improve the existing processes; (ii) enhance performance, (iii) increase time efficiency; and (iv) improve work accuracy. A new model that focuses on low-performance processes has been designed. The proposed model is also used to develop KPIs that are measurable and capable of detecting flaws and identify the possible improvements. When the model is continuously applied by service providers, the waiting time and non-adding value activities are expected to be significantly minimized. Likewise, monitoring and control of internal processes and activities can be improved. Furthermore, lean management is advantageous for the telecommunication sector as it allows a quick response to rapid changes in the telecom technology and, thus, improves the customer satisfaction.